Systematic Study of Key Components for a Coaxial-Cavity Gyrotron for DEMO - Franck, Joachim (Karlsruher Forschungsberichte aus dem Institut für Hochleistungsimpuls- und Mikrowellentechnik, 2017)
The physical design of cavity and magnetron injection gun (MIG) for a realistic, DEMO-compatible, coaxial-cavity 238 GHz 2 MW CW fusion gyrotron is developed in this work, having auxiliary frequencies at 170 GHz and 204 GHz. Novel systematic approaches towards multi-frequency mode selection, magnet requirements, and MIG design are presented. Mode deterioration and voltage depression variation due to insert misalignment versus cavity wall and/or versus electron beam are studied.